Analysis of Factors Influencing Career Interest in Taxation - Mulyanto; Diah Ayu Susanti; Alicia Fenny Savatra (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
Graduates in accounting are expected to possess both soft and hard skills, particularly in taxation. This study aims to examine the influence of perceptions of taxation, tax knowledge, self-confidence, and job market considerations on students’ interest in pursuing a career in taxation. The research was conducted among accounting students from universities in Kudus Regency, using purposive sampling with 313 respondents who had taken taxation courses. The data analysis method used was structural equation modelling with partial least squares (SEM-PLS), processed using smart-PLS 4.1.0.2. The results show that perceptions of taxation, tax knowledge, self-confidence, and job market considerations all have a positive effect on students' career interest in the field of taxation. This study highlights the importance of both cognitive and psychological factors in shaping students’ career aspirations. Additionally, it offers insight into how perceptions and confidence, alongside external market considerations, contribute to professional interest in taxation. The findings provide valuable input for educators and policymakers to better design curriculum and career guidance. This research contributes to the limited empirical literature on tax career interest among Indonesian accounting students and underscores the relevance of aligning educational outcomes with labor market demands. Abstrak - Lulusan akuntansi dituntut memiliki hard skill dan soft skill, khususnya di bidang perpajakan. Penelitian ini bertujuan untuk menganalisis pengaruh persepsi tentang perpajakan, pengetahuan perpajakan, kepercayaan diri, dan pertimbangan pasar kerja terhadap minat berkarir di bidang perpajakan. Kompetensi dan keterampilan di bidang perpajakan menjadi faktor penting dalam mencetak lulusan profesional yang mampu bersaing di dunia kerja. Penelitian dilakukan pada mahasiswa akuntansi di perguruan tinggi di Kabupaten Kudus dengan metode purposive sampling, melibatkan 313 responden yang telah menempuh mata kuliah perpajakan. Analisis data menggunakan metode SEM-PLS dengan bantuan software SMART-PLS 4.1.0.2. Hasil penelitian menunjukkan bahwa keempat variabel independen memiliki pengaruh positif terhadap minat karir di bidang perpajakan. Temuan ini menunjukkan pentingnya penguatan persepsi positif, peningkatan pengetahuan, serta pengembangan kepercayaan diri dan pemahaman tentang pasar kerja untuk membentuk minat karir mahasiswa. Penelitian ini juga menyoroti bagaimana pendekatan strategis dan psikososial dapat memperkuat kesiapan lulusan dalam menghadapi tantangan profesi perpajakan di masa depan. Kontribusi ini relevan bagi pengembangan kurikulum dan kebijakan pendidikan tinggi akuntansi di Indonesia.